The FABC Vision of Dialogue as an Appropriate Approach for the Catholic Church in Vietnam in its Mission of Evangelization Today - Tran Hoan Chinh, (Archīum Ateneo, 2021)
Similar to many Asian countries, the Catholic Church in Vietnam is still a minority which is challenged by the reality of poverty and injustice, social and political conflicts, the increase of migrants, pollution and environmental crisis, corruption and moral degradation, the plurality of cultures and religious traditions. This complex context and the urgent need for being “a missionary Church in Asia” and in seeking to attain a “new way of being the Church in Asia” raise questions concerning the vision of the Catholic Church in Vietnam and her evangelizing mission. This study aims to show how dialogue theologically and pastorally becomes one of the most important priorities of the Federation of Asian Bishops’ Conferences (FABC) for its evangelizing mission in the context of the multi-religious and pluricultural reality of contemporary Asia in general and the local Church in Vietnam in particular. Dealing with the situation of the Church’s evangelizing mission in a communist-run country like Vietnam, this study opens with an in-depth analysis and exploration of the pastoral vision of the Catholic Bishops’ Conference of Vietnam (CBCV) in its important pastoral letters, especially the 1980 Pastoral Letter; this is approached through the lense of the FABC vision of dialogue. Then the study continues showing how the Catholic Church in Vietnam translate the FABC vision of dialogue to better fulfill her mission of evangelization today. The thesis concludes by focusing particularly on the dialogue between the Church and the Vietnamese government, analyzing some initiatives of the local Church facing the urgent need of its evangelizing mission; it especially proposes some pastoral v suggestions relevant to the dialogical approach to the evangelizing mission of the Church in Vietnam.